Interferon gamma, an important marker of response to immune checkpoint blockade in non-small cell lung cancer and melanoma patients. (13th January 2018) - Karachaliou, Niki; Gonzalez-Cao, Maria; Crespo, Guillermo; Drozdowskyj, Ana; Aldeguer, Erika; Gimenez-Capitan, Ana; Teixido, Cristina; Molina-Vila, Miguel Angel; Viteri, Santiago; De Los Llanos Gil, Maria; Algarra, Salvador Martin; Perez-Ruiz, Elisabeth; et al.
Background: Programmed death-ligand 1 (PD-L1) may be induced by oncogenic signals or can be upregulated via interferon gamma (IFN-γ). We have explored whether the expression of IFNG, the gene encoding IFN-γ, is associated with clinical response to the immune checkpoint blockade in non-small cell lung cancer (NSCLC) and melanoma patients. The role of inflammation-associated transcription factors STAT3, IKBKE, STAT1 and other associated genes has also been examined. Methods: Total RNA from 17 NSCLC and 21 melanoma patients was analyzed by quantitative reverse transcription PCR. STAT3 and Rantes, YAP1 and CXCL5, DNMT1, RIG1 and TET1, EOMES, IFNG, PD-L1 and CTLA4, IKBKE and NFATC1 mRNA were examined. PD-L1 protein expression in tumor and immune cells and stromal infiltration of CD8 + T-cells were also evaluated. Progression-free survival and overall survival were estimated. Results: A total of 17 NSCLC patients received nivolumab and 21 melanoma patients received pembrolizumab. Progression-free survival with nivolumab was significantly longer in NSCLC patients with high versus low IFNG expression (5.1 months versus 2 months, p = 0.0124). Progression-free survival with pembrolizumab was significantly longer in melanoma patients with high versus low IFNG expression (5.0 months versus 1.9 months, p = 0.0099). Significantly longer overall survival was observed for melanoma patients with high versus low IFNG expression (not reached versus 10.2 months p = 0.0183). There was a trend for longer overall survival for NSCLC patients with high versus low IFNG expression. Conclusions: IFN-γ is an important marker for prediction of response to immune checkpoint blockade. Further research is warranted in order to validate whether IFNG is more accurate than PD-L1.